Teoremas de Green, Gauss e Stokes e algumas aplicações - Silva Júnior, Gustavo Alexandre de Araújo (Universidade Federal Rural do Semi-Árido, 2020)
Science and Technology students feel a great difficulty in relating the theoretical subjects studied in class with applications in the area of their respective engineering. This work shows some applications in the engineering of concepts studied in the discipline of introduction to the functions of several variables. The concepts covered in the calculation disciplines are of paramount importance for engineering, as they are the pillars of any area that the engineer may work on. In this work we study the Green, Stokes and Gauss Divergence Theorems, results applicable mainly in the area of fluid flow. The objective of this work is to show the applications of these theorems in the engineering area, for example, in electrical engineering. In addition to demonstrating the above theorems, we present some applications focused on engineering.
Keywords: Teorema de Green; Teorema de Stokes; Teorema da Divergência de Gauss; Aplicações; Green's theorem; Stokes theorem; Gauss Divergence Theorem; Applications; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA